EVALUATION OF COMPETITIVENESS IN THE APPAREL MARKET THROUGH PANEL RESEARCH - ASKAROVA MAVLUDA TURAPOVNA; RADJABOV BUNYOD ABDUHALILOVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
Satisfaction with demand for essential goods for society is an important issue for any country and the basis for determining the standard of living of the population. Analyzing the state of the garment market and setting strategic goals for future changes is of vital importance. The article describes the feasibility of using the panel research tool to evaluate the ready-to-wear market and its changes.